Editor’s Note Volume 13 No 1 - Shan, Rebecca (Bellarmine Law Society Review, 2023)
In the first issue of the Bellarmine Law Society Review’s thirteenth volume, two undergraduate contributors explore a range of topical issues through the lens of legal analysis. First, Sunderya Ulziibold explores the topical issues of COVID-19 vaccine intellectual property rights by exploring the history of intellectual property rights and contextualizing the issue through the Moderna v. Pfizer/BioNTech case. Second, Lila Zarrella analyzes the Equal Rights Amendment and potential for its ratification, ultimately arguing that despite some shortcomings, the ERA might represent the most applicable and feasible opportunity to cement gender equality under law.